Black TV : five decades of groundbreaking television from Soul train to Black-ish and beyond - Butler, Bethonie (Black Dog & Leventhal Publishers, 2023)
"The first of its kind, this illustrated gift book, written by veteran Washington Post TV reporter Bethonie Butler, is a comprehensive look at the rich history of groundbreaking--and often underappreciated--television shows with leading Black characters from the last fifty years"--